2005
DOI: 10.1002/chin.200551127
|View full text |Cite
|
Sign up to set email alerts
|

2‐Alkyl‐3‐(1,2,3,6‐tetrahydropyridin‐4‐yl)‐1H‐indoles as Novel 5‐HT6 Receptor Agonists.

Abstract: Pyridine derivatives R 0380 2-Alkyl-3-(1,2,3,6-tetrahydropyridin-4-yl)-1H-indoles as Novel 5-HT 6 Receptor Agonists. -A series of the title indole derivatives [cf. (VI)] are synthesized and evaluated for their 5-HT6 activity. Compound (VIa) proves to be the most potent agonist in this series. -(MATTSSON*, C.; SONESSON, C.; SANDAHL, A.; GREINER, H. E.; GASSEN, M.; PLASCHKE, J.; LEIBROCK, J.; BOETTCHER, H.; Bioorg. Med. Chem. Lett. 15 (2005) 19, 4230-4234; Med. Chem., Biotech Cent., Carlsson Res. AB, S-413 46 Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…49 The hit compound 5 (EMD-386088) behaved as a full 5-HT 6 R agonist (EC 50 = 1.0 nM) and provided good selectivity over all other serotonin receptors (>15-fold) except for 5-HT 3 R (IC 50 = 34 nM). Interestingly, the opposite antagonistic activity can simply be obtained with the introduction of a phenylsulfonyl group in the indole N-1 position (6, IC 50 = 2 nM).…”
Section: Design Of 5-ht 6 R Agonistsmentioning
confidence: 99%
“…49 The hit compound 5 (EMD-386088) behaved as a full 5-HT 6 R agonist (EC 50 = 1.0 nM) and provided good selectivity over all other serotonin receptors (>15-fold) except for 5-HT 3 R (IC 50 = 34 nM). Interestingly, the opposite antagonistic activity can simply be obtained with the introduction of a phenylsulfonyl group in the indole N-1 position (6, IC 50 = 2 nM).…”
Section: Design Of 5-ht 6 R Agonistsmentioning
confidence: 99%
“…pre-treatment with the selective 5-HT 4 [ML-10302 (Yang et al, 1997)], 5-HT 6 [EMD-386088 (Mattsson et al, 2005)] and 5-HT 7 [LP-12 (Leopoldo et al, 2007)] receptor agonists increased 0.5% formalin-induced secondary allodynia and hyperalgesia. Furthermore, i.t.…”
Section: Involvement Of 5-ht 4/6/7 Receptors In Development Of Formalmentioning
confidence: 99%
“…More recently, several research groups have identified selective, high-affinity 5-HT 6 receptor full and partial agonists Glennon et al 2000;Holenz et al 2005;Mattsson et al 2005;Romero et al 2006Romero et al , 2007Schechter et al 2004Schechter et al , 2007. The few investigations carried out to date suggest that 5-HT 6 receptor agonists impair recognition memory in social recognition (Loiseau et al 2008) and short-and long-term memories in autoshaping tasks (Meneses et al 2008).…”
Section: Introductionmentioning
confidence: 95%
“…1), a potent agonist at rat 5-HT 6 receptors. E-6801 was compared with two well-established 5-HT 6 receptor antagonists, SB-271046 (5-Chloro-N-(4-methoxy-3-(piperazin-1-yl) phenyl)-3-methyl-2-benzothiophenesulfonamide) (Bromidge et al 1999) and Ro 04-6790 (4-amino-N-(2,6 bis-methylaminopyrimidin-4-yl)-benzene sulphonamide) (Sleight et al 1998), and the agonist, EMD-386088 (5-Chloro-2-methyl-3-(1,2,3,6-tetrahydro-4-pyridinyl)-1H-indole) (Mattsson et al 2005).…”
Section: Introductionmentioning
confidence: 99%